The DUMP Campaign - Henman, Martin (green cross publishing, 2009)
From an initial group of six pharmacies in 2002, now every pharmacy in the area is a part of the DUMP initiative, which urges consumers to `Dispose of Unused Medication Properly? and attempts to achieve this by encouraging patients to return unused medicines to their local pharmacy. The quantity of pharmaceuticals collected in the pilot for six weeks was 108kg. This rose signi?cantly to 4.47 tonnes for the ?rst full year of collection (2004) when all pharmacies were involved. Year on year, the quantity being collected has increased signi?cantly with total of 12 tonnes collected in 2007.
PUBLISHED
Keywords: medicines; patient safety; medications; public health